Objetos pronominales del quechua - Plaza M., Pedro (1987)
The grammatical category of Person (P) is very important in the Quechua worldview (see for example Plaza 1980b). Following the point of view of Hardman (1972), the Person in Quechua constitutes a linguistic postulate, since its importance in Quechua culture expressly manifests itself in various ways in its grammar. Among the Personal Pronouns (which we will see later). Possessives, and verbal endings or conjugation. In this article we will not review all the possible forms of grammatical expression that correspond to what we call Pronominal Relations (R.P.). We will limit ourselves to considering those that are expressed by means of suffixes that are part of the conjugation and are sensitive to the modes and tenses of the verb.